2020
DOI: 10.2147/jir.s262132
|View full text |Cite
|
Sign up to set email alerts
|

<p>Recent Updates on Anti-Inflammatory and Antimicrobial Effects of Furan Natural Derivatives</p>

Abstract: The furan nucleus is found in a large number of biologically active materials. In recent years, many natural furan derivatives were isolated and their biological effects were investigated. In this review, we focused on the anti-inflammatory and antimicrobial effects of some natural furans and discussed their effects on the immune system. Our investigation revealed that furan natural derivatives have effective antioxidant activities and exert regulatory effects on various cellular activities by modifying some s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 99 publications
0
36
0
1
Order By: Relevance
“…Heterocyclic compounds in particular oxygen containing heterocycles represent an important class of compounds possessing interesting pharmacological and biological activities [21][22][23] . Benzofuran nucleus, as a key functional scaffold, represents a basic structure in a diversity of biologically active synthetic and natural products [24][25][26] , with broad range of desirable activities including; anti-Alzheimer's 27 , antibacterial 28 , anti-tubercular 29 , antioxidant 30 , anti-inflammatory 31 , as well as antitumor activities 32 . Benzofuran derivatives exert their antiproliferative activity with diversified mechanisms such as inhibition of tubulin polymerisation 33,34 , HIF-1 35 , Aurora B kinase 36 and VEGFR-2 activity 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds in particular oxygen containing heterocycles represent an important class of compounds possessing interesting pharmacological and biological activities [21][22][23] . Benzofuran nucleus, as a key functional scaffold, represents a basic structure in a diversity of biologically active synthetic and natural products [24][25][26] , with broad range of desirable activities including; anti-Alzheimer's 27 , antibacterial 28 , anti-tubercular 29 , antioxidant 30 , anti-inflammatory 31 , as well as antitumor activities 32 . Benzofuran derivatives exert their antiproliferative activity with diversified mechanisms such as inhibition of tubulin polymerisation 33,34 , HIF-1 35 , Aurora B kinase 36 and VEGFR-2 activity 37 .…”
Section: Introductionmentioning
confidence: 99%
“…58 Furan-based substituted compounds showed up-and-coming biological applications such as anti-cancer, antimicrobial, anti-hyperglycemic, and analgesic. 59 The DpK a value of FTCA (pK a ¼ 2.38) with 2-AP (pK a ¼ 3.62) is 1.24, and it lies in the elusive DpK a range. The generalization predicted the proton transfer between FTCA and 2-AP due to the presence of more than two -I effect groups on the aromatic tetrahydrofuran ring.…”
Section: Resultsmentioning
confidence: 94%
“…In this sense, we found interesting the differences observed in the biological activity of 2-acetyl-thiophene and 2-acetyl-furan rings. The furan ring is found in a large number of biologically active, natural molecules, and many furan-containing derivatives exhibit extensive pharmacological activities [ 45 ]; indeed, 2-acetyl-furan has been detected as a volatile component of pine leaves, French lavender and chestnuts honey, that proved to possess high antimicrobial potential [ 46 ], and has been demonstrated to be also the most abundant compound characterizing the Perilla frutescens essential oils that, tested against different Aspergillus species comprising A. flavus , showed potent antifungal effect [ 47 ]. However, our data showed that, while 2-acetyl-thiophene and 2-acetyl-furan are fundamentally inactive, their thiosemicarbazones inhibit aflatoxin biosynthesis in A. flavus .…”
Section: Discussionmentioning
confidence: 99%